The extended ‘chilling’ effect of Facebook: The cold reality of ubiquitous social networking - Marder, Ben; Joinson, Adam; Shankar, Avi; Houghton, David (Computers in human behavior, 2016)
Prior research has established the phenomenon of the ‘Chilling Effect’ where people constrain the self they present online due to peer-to-peer surveillance on Social Network Sites (SNS). However currently uninvestigated is the possibility that the threat of such surveillance on these sites might constrain the self presented offline in ‘reality’, known here as ‘the extended chilling effect’. The purpose of this study is to examine the existence of this ‘extended chilling effect’. Drawing on theories of self-awareness and self-presentation, the impact of surveillance in SNS is theorized to lead to an awareness of online audiences in offline domains, stimulating a self-comparison process that results in impression management. A mixed methods study of semi-structured interviews (n = 28) and a 2 × 2 between-subjects experiment (n = 80), provides support for offline impression management in order to avoid an undesired image being projected to online audiences. The novel finding that the chilling effect has extended highlights the potential dangers of online peer-to-peer surveillance for autonomy and freedom of expression in our offline lives. •Accounts provided of ‘chilled’ behavior offline due to online surveillance.•Model tested for the process underlying the ‘chilling’ of behavior offline.•Saliency of Facebook offline increases public self-awareness.•Support provided for the ‘extended chilling’ effect of Social Network Sites.